Improving the Performance of Solar Power Plants through IOT and Predictive Data Analytics - Begum, Shahida; Banu, Reshma (International Journal of Computer Sciences and Engineering, 2018)
IOTTo increase the utilization and development of solar energy which is Eco friendly. Weather Predication is done in order to improve the performance and maintain its consistency for long term to deliver secure and reliable power while managing uncertainties. In order to enhance and improve the performance, preventive maintenance of solar power plant is done by implementing Operation & Maintenance (O&M)activities using predictive analytics and supervisory control and data acquisition (SCADA). With the help of internet(cloud)along with IOT devices, Operation and maintenance, Supervisory Control And Data Acquisition the preventive maintenance can be improved. Many industries in India are working towards increasing the performance ratio of solar power plants in large scale. This paper presents a comparative study to improve the performance of solar power plants through IOT and predictive analytics.